Test Various Media Against Lettuce Plant Growth (Lactuca Sativa L.) Hydroponics. - Agus Trikoriantono (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
This research was conducted in STIPER Muhammadiyah Tanah Grogot for 3 (two) months. This study aims to determine the effect of planting media usage and proper nutrition on the growth of lettuce plants with hydroponics system.The experimental design used was a two factor factorial and three replications arranged in a randomized block design (RAK). The first factor was using treatment of planting medium consisting of three levels, namely P1 = Using sawdust planting media, P2 = using the medium of husk charcoal planting, P3 = using the planting medium of straw. The second factor is using Nutrition Addition treatment consisting of two levels, namely Q1 = Using Good Plant Nutrition, Q2 = Using Hydro J Nutrition.The results showed that: Planting media (P) has a significant effect on stem diameter. In the treatment of Nutrition (Q) has significant effect on leaf number, stem diameter and root length, and very significant effect on plant weight. The interaction treatment between planting medium and nutrient feeding significantly affected the growth of plant height and number of leaves.